Pop up Peekaboo! Rainforest - Carle Lloyd (London Dorling Kindersley Publishing, 2022)
Climb through the layers of the busy rainforest and discover lots of animals along the way. Babies and toddlers will love lifting the big flaps to find five peekaboo surprises pop up from the pages - a funny anteater with a very long tongue, a spotty jaguar leaping into a busy river, a slithery snake hanging from a leafy tree, a beautiful hummingbird sipping sweet nectar from a pretty flower, and two playful monkeys climbing to the treetops
Early Years